Anthropogenic activities accelerate LULC conversion and only a sustainable development scenario is optimal for agro-pastoral ecotone development - Jing Jin; Zilong Liao; Tiejun Liu; Mingxin Wang; Jing Zhang; Xinjian Zhang; Yining Fan (Scientific Reports)
Abstract Despite the ecological and socioeconomic importance of agro-pastoral ecotones, changes in land use and land cover (LULC) and their driving mechanisms are not comprehensively understood. In this study, a systematic framework for LULC assessment covering comprehensive timeframes was constructed for the Tabu watershed. Results demonstrated that a new process of LULC changes began in 1998, with a significant increase in farmland and decrease in grassland. The increase in dynamic degrees and structural variation coefficients indicated intensive and frequent changes in LULC. Conversion ratios between grassland and farmland exceeded 95%, and construction land encroached upon grassland. Grassland changes were driven mainly by natural factors based on the random forest regression, as well as changes in farmland and construction land. The influence of anthropogenic drivers on LULC became significant. Under the sustainable development scenario, the increase in grassland with a high fractional vegetation cover in 2034 was the most significant, the area of bare land decreased, the area of construction land steadily increased, and the reduction in farmland area was under control. Under this scenario, both socioeconomic development and ecosystem stability can be achieved. This study provides insights into regional land dynamics and provides systematic guidance for sustainable land management.